Electromagnetic Beam Scattering From Planar Surfaces - Yıldırım, Osman; Tere, Mehmet Fatih; Kılıç, Ali (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2011)
Nondestructive techniques by using electromagnetic waves in many disciplines such as agriculture, engineering geology, material sciences and so on are very important regarding predictions. As it is well-known, material properties can be determined by using electromagnetic waves. The scattering of electromagnetic waves due to physical and geometrical discontinuity is creating surface waves which are still dominant in prediction of material properties. A dielectric sheet on the ground plane will act as a guiding structure for surface waves. Matching the magnetic and electric field components across the air-dielectric boundary gives surface wave modes. In this research, beam wave scattering from planar surfaces is analyzed by including a comparison to the electromagnetic waves.
Keywords: electromagnetic waves; beam; scattering; diffraction; elektromanyetik dalgalar; kiriş; saçılma; kırınım